2010
DOI: 10.1051/eas/1042022
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of Earth-like Planets in Multi-Planet Systems: Preliminary Report

Abstract: We ask if Earth-like planets (terrestrial mass and habitable-zone orbit) can be detected in multi-planet systems, using astrometric and radial velocity observations. We report here the preliminary results of double-blind calculations designed to answer this question.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 3 publications
(4 reference statements)
1
15
0
Order By: Relevance
“…The dominant factor will rather be the instrumental precision. Note that if present, other larger planets will also induce noise, which is not considered in this paper, but the series of blind tests conducted to estimate the detection capabilities of Earth-like planets in multiple systems by space-borne astrometry (Traub et al 2010) have shown that this noise can be well circumvented.…”
Section: Planet Detection In Astrometrymentioning
confidence: 99%
“…The dominant factor will rather be the instrumental precision. Note that if present, other larger planets will also induce noise, which is not considered in this paper, but the series of blind tests conducted to estimate the detection capabilities of Earth-like planets in multiple systems by space-borne astrometry (Traub et al 2010) have shown that this noise can be well circumvented.…”
Section: Planet Detection In Astrometrymentioning
confidence: 99%
“…NASA conducted a double blind study for the astrometric detection of Earth-like planets in multiple planet systems (Traub et al 2010). The result of the test was that the presence of multiple planets has a marginal to negligible impact on the astrometric mission's ability to detect and measure the orbits of terrestrial planets (planets of mass 1 to 10 M ⊕ ) in the HZ.…”
Section: Astrometric Orbit Precisionmentioning
confidence: 99%
“…Core accretion models predict a peak in the planet population near 10-30 M ⊕ composed of planets that did not manage to reach the stage of runaway gas accretion (Mordasini et al 2009). For an astrometric mission such as SIM Lite, it is not significantly harder to find an exo-Earth in a multiple planet system than it would be if the exo-Earth were alone (Traub et al 2010). Current studies of direct imaging missions do not address the problem of confusion due to multiple planets (Brown 2005;Savransky et al 2009aSavransky et al , 2009bSavransky et al , 2010.…”
Section: Modeling Realistic Planet Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the increased sensitivity of instruments, astronomers have found that there are many more small exoplanets than giant, gaseous ones. According to recent estimates, [1][2][3][4][5] there are at least 10% of stars that would have a small planet orbiting in their habitable zone (HZ).…”
Section: Introductionmentioning
confidence: 99%